2008
DOI: 10.1021/jp711334f
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio Study of Reduction of V2O5 through the Formation of Oxygen Vacancies and Li Intercalation

Abstract: Two methods of reduction of V 2 O 5 have been investigated: oxygen vacancy formation and lithium intercalation. The electronic structure, geometry, and energetics of these reduced systems are examined. Oxygen vacancies in bulk R-V 2 O 5 have been investigated by using gradient-corrected density functional theory (GGA) and density functional theory corrected for on-site Coulomb interactions in strongly correlated systems (GGA+U). The GGA calculation predicts a delocalized defect electronic state. This disagrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
222
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 232 publications
(257 citation statements)
references
References 65 publications
33
222
2
Order By: Relevance
“…In contrast, an early optical study reported an optical band gap of approximately 4.0 eV resulting from indirect transitions [1]. The calculated optical band gap in this study is in good agreement with the low end of the experimental range, consistent with the PBE functional (and other GGA functionals) underestimating band gaps [104]. …”
Section: Energy (Ev)supporting
confidence: 77%
“…In contrast, an early optical study reported an optical band gap of approximately 4.0 eV resulting from indirect transitions [1]. The calculated optical band gap in this study is in good agreement with the low end of the experimental range, consistent with the PBE functional (and other GGA functionals) underestimating band gaps [104]. …”
Section: Energy (Ev)supporting
confidence: 77%
“…These predictions of metallic behavior are incompatible with the localized defect state indicated by experimental photoabsorption 10 and disagree qualitatively with previous Hartree-Fock calculations. 48 Standard DFT functionals ͑local density or general gradient approximations͒ often fail to predict correct electronic structures for reduced transition metal oxides, [58][59][60] due to the self-interaction error inherent to such functionals, 61,62 and which is acute for highly localized d and f valence states. This has been discussed previously for a number of reduced TiO 2 systems.…”
Section: 12mentioning
confidence: 99%
“…64 This opens a gap between occupied and unoccupied states for the orbitals of interest and gives improved descriptions of polaronic defect states in a number of oxides. [59][60][61]65 Richter et al 66 have previously demonstrated that GGA+ U reproduces the experimental splitting between occupied and unoccupied Ti 3d states in lithium titanate ͑Li 0.5 TiO 2 ͒, although the corresponding charge density was not presented, and this method has not yet been applied to the low concentration lithiated-anatase phase.…”
Section: 12mentioning
confidence: 99%
“…Reduction of V 2 O 5 through the formation of oxygen vacancy, V O , defects have been studied both by theoretical and experimental studies. 10,11,12,13,14,15 In this work, we address some of the key unanswered questions regarding the correlation between optical properties and electronic structure of The rise of absorbance in the NIR spectral range in reduced oxide is a result of optical excitation of V O defect related mid-gap states. In addition, using in-situ Raman measurements during reduction process, we show that the oxygen atom that most readily participates during electrochemical reduction at room-temperature and gets reduced is the three-fold coordinated oxygen (O3).…”
Section: Introductionmentioning
confidence: 99%